Editorial: Antimicrobial resistance in food-producing environments: a One Health approach - Agga, G.E.; Amenu, Kebede (Frontiers Media, 2024)
The One Health High-Level Expert panel comprised of the United Nations Food and Agriculture Organization (FAO), the United Nations Environment Program (UNEP), the World Health Organization (WHO), and the World Organization for Animal Health (WOAH; founded as OIE) defines One Health as “an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals and ecosystems. It recognizes that the health of humans, domestic and wild animals, plants, and the wider environment (including ecosystems) are closely linked and interdependent. The approach mobilizes multiple sectors, disciplines and communities at varying levels of society to work together to foster well-being and tackle threats to health and ecosystems, while addressing the collective need for clean water, energy and air, safe and nutritious food, taking action on climate change, and contributing to sustainable development.” (Mettenleiter et al., 2023). There is nothing more fitting than antimicrobial resistance (AMR) to the principles of One Health, which provides a framework for an interdisciplinary approach to dealing with this global challenge (FAO, 2016; Robinson et al., 2016; Lancet, 2023).